Caracterización bacteriológica de frutas expendidas en supermercados de Riobamba - María Pamela, Cabay Asadobay (2020)
Today bacterial resistance has become one of the worldwide health problems, developing a large increase because of the selective pressure to use antibiotics in a large scale, leaving no alternatives for bacterial infections treatments. The purpose of this study is to determine the antimicrobial resistance of isolated pathogenic bacteria in fruits obtained at supermarkets in the city of Riobamba. This is a descriptive, cross-sectional and field work, which shows the existence of pathogens that cause infections in the gastrointestinal tract. The fruits were taken from five stores located in strategic points of the city. For the bacterial isolation and identification, Blood, McConkey and CLED agar were used, while biochemical and physiological tests were used to classify the bacteria in genus and species. Antimicrobial resistance and susceptibility were measured by the colony isolation technique using the Kirby-Bauer method. The results show the presence of 11 bacteria, the Enterobacteriaceae is found with a 78.38% present with Citrobacter amanolaticus, Citrobacter freundii, Citrobacter diversus, Klebsiella pneumoniae, Enterobacter aerogenes, Morganella morganii, Enterobacter cloacae, Pseudomona aeruginosa, Escheria, and Lach Enterococcaceae with 21.62%, Enterococcus sp and Staphylococcus negative coagulase. The results obtained show that most bacteria showed greater susceptibility to antibiotics. Finally, it follows that agricultural goods are contaminated by pathogenic bacteria that put human health at risk.